Bringing Feminist Perspectives into Community Informatics - Peddle, Katrina; Powell, Alison; Shade, Leslie Regan (Atlantis)

(untitled) (Mount Saint Vincent University, 2008)
Through analysis of two Canadian Research Alliance for Community Innovation and Networking (CRACIN) case studies this paper argues that feminist perspectives strengthen community informatics (CI) theory. While feminist CI has addressed the dynamics of access and intricacies of technological design, labor, both gendered and invisible, is one area that needs further refinement in CI.